PENGARUH PERSEPSI KEBERMANFAATAN, PERSEPSI KEMUDAHAN SERTA KEAMANAN DAN KERAHASIAAN TERHADAP PENGGUNAAN E-FILING WAJIB PAJAK UMKM - Hani Chairani; Khoirina Farina (LPPM POLITEKNIK LP3I BANDUNG, 2021)
The purpose of this study was to determine the effect of perceived usefulness, perceived convenience as well as security and confidentiality on the use e-filing of MSME taxpayers. A total of 100 taxpayer respondents were selected as the research sample. With a location in Pasar Tanah Abang Blok B Jakarta. The research data is primary data, namely distributing questionnaires to respondents. The purposive sampling method was used in this study in relation to sample collection. The data analysis method used descriptive analysis, verification and hypothesis testing using the SmartPLS version 3.2.9 program. The test results of the coefficient of determination (R2) are 84% which indicates that the use of e-filing can be influenced by perceptions of usefulness, perceptions of convenience as well as security and confidentiality. While the remaining 16% is influenced by other variables outside the research variables. The results of this study indicate that there is a positive and significant influence on perceived usefulness, perceived ease of use of e-filing, as well as security and confidentiality on the use e-filing of MSME taxpayers